Mathematical Creative Thinking Ability in terms of the Habits of Mind in PBL with a Management System with a Goal Free Problems strategy - Pradinar, Fanindya Dwisetiya; Pujiastuti, Emi (Unnes Journal of Mathematics Education, 2022)
Problem Based Learning with a Management System with a Goal Free Problems strategy is given to improve the mathematical creative thinking skills of class X MIPA students at SMA Negeri 8 Semarang which are not yet optimal. . Purpose main from study this is analyze ability think learners reviewed from Habits of Mind , as consequence from application of learning models Problem Based Learning help The LMS is Google Classroom . Method research used _ that is mixed methods with posttest only control design . Sample taken two class with technique random sampling from population class X MIPA 8 Semarang . Experiment class use PBL model with Management System with Goal Free Problems strategy whereas class control using the PBL model. Subject in research this as much 8 student from class experiment . Qualitative data analysis i.e. result data interview and results test mathematical creative thinking skills subject research . Research results showing that : (1) ability think creative mathematical participant educate reviewed from Habits of Mind in PBL with Management System reach more from criteria minimum completeness is 68; (2) ability think creative mathematical participant educate reviewed from Habits of Mind in PBL with Management System reach completeness classic that is more from 75% of participants educate reach limit complete ; (3) average ability think creative mathematical reviewed from Habits of Mind in PBL with Management System more tall from Problem Based Learning model learning ; (4) proportion completeness results test ability think creative mathematical reviewed from Habits of Mind in PBL with Management System more tall from Problem Based Learning model learning ; (5) ability think creative mathematical with four indicator think creative is in the subject category Persisting , Thinking about Thinking , Thinking Flexibly , and Applying Past Knowledge to New Situations .